Positive electrode active material, preparation method thereof, positive electrode plate comprising positive electrode active material, battery and electric device
Patent Information
- Application Number
- CN202380066898.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-31
- Publication Date
- 2025-04-29
AI Technical Summary
The cathode material of existing secondary batteries has cation mixed discharge phenomenon in the high voltage charge and discharge cycle, resulting in structural changes and particle cracking, which in turn deteriorates the cycling performance and energy density of the battery.
Using a ternary positive electrode material containing layered crystal structure and perovskite structure, the structural stability and lithium ion diffusion performance of the material are improved through the design of symbiotic structure and stress release sites. The preparation method includes coprecipitation reaction and step-by-step calcination Craft.
It significantly improves the energy density and cycling performance of the battery, reduces the risk of cracking of the positive electrode material particles, and enhances the structural stability of high-voltage charging and discharge.
Smart Images

Figure CN119908043A_ABST
Abstract
Description
Positive electrode active material, preparation method thereof, positive electrode sheet, battery and electrical device containing the same Technical Field
[0001] The present application relates to a positive electrode active material, a preparation method thereof, a positive electrode sheet, a battery and an electrical device containing the same. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in many fields such as electric tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, etc. With the application and promotion of secondary batteries, the requirements for their energy density have become gradually stricter.
[0003] Summary of the Invention
[0004] The present application provides a positive electrode active material and a preparation method thereof. The positive electrode active material can improve the energy density and cycling performance of a battery containing the same; the present application also provides a positive electrode sheet, a battery and an electrical device containing the positive electrode active material.
[0005] In a first aspect, an embodiment of the present application provides a positive electrode active material, including a ternary positive electrode material. The ternary positive electrode material includes a layered crystal structure and a perovskite structure.
[0006] Without being bound by any theory or explanation, the perovskite structure has the property of zero strain. The so-called "zero strain" means that when lithium ions are inserted or extracted from its crystal, both the lattice constant and the volume change are very small, for example, less than 1%. In other words, during the charge-discharge cycle, this "zero strain" can inhibit the structural damage caused by the back-and-forth expansion and contraction of the electrode material. Therefore, when the ternary positive electrode material includes a perovskite structure, on the one hand, the perovskite structure can coexist with the layered crystal structure to maintain the stability of the layered crystal structure, and on the other hand, it can serve as a stress release site to release the stress accumulated by the ternary positive electrode material during the cycle, thereby inhibiting the cracking of the ternary positive electrode material particles and improving the structural stability of the ternary positive electrode material. Thus, the structural stability of the positive electrode active material during high-voltage charge-discharge cycles can be improved, and the capacity utilization of the positive electrode active material can be enhanced, enabling the battery to have both high energy density and good cycling performance.
[0007] In any embodiment of the present application, the perovskite structure includes La t M 1-t NiO3-type perovskite structure, where 0 < t < 1, and M includes one or more of Ca, Ti, Fe, Mg, Zn, Zr, Nb, W, Ta, Mo, Cu.
[0008] La t M 1-tThe NiO3 perovskite structure has zero strain properties and a suitable volume, which can be doped into the layered crystal structure of the ternary cathode material, forming a stable symbiotic structure with the layered crystal structure. This can further enhance the structural stability of the ternary cathode material, thereby improving the battery's cycling performance.
[0009] In any embodiment of the present application, in the ternary positive electrode material, the molar ratio of Ni element to the transition metal element is greater than or equal to 0.6.
[0010] In any embodiment of the present application, the ternary cathode material has the general formula Li 1+a [Ni x Co y Mn z La m M n ]O2, where 0.6≤x<1, 0≤y≤0.4, 0≤z≤0.4, 0.05≤a≤0.1, 0 <m≤0.1,0<n≤0.1,x+y+z+m+n=1。
[0011] Optionally, 0.02≤m≤0.05, 1≤m / n≤2.
[0012] The above-mentioned ternary positive electrode material has a high nickel content, thus having a high theoretical capacity. In addition, the above-mentioned ternary positive electrode material also contains an appropriate amount of La t M 1-t NiO3 type perovskite structure, appropriate amount of La t M 1-t The NiO3 perovskite structure can effectively stabilize the layered crystal structure of the ternary cathode material, thereby improving the structural stability of the ternary cathode material under high-voltage charge-discharge cycles. This helps reduce the risk of particle cracking in the ternary cathode material and improves the capacity and cycle stability of the ternary material.
[0013] In any embodiment of the present application, based on the total molar amount of the ternary positive electrode material, the molar percentage of the perovskite structure is 1%-10%, and can be optionally 2%-5%. When the molar percentage of the perovskite structure is within the above-mentioned appropriate range, the ternary positive electrode material can have good lithium ion diffusion performance while maintaining the stability of the layered crystal structure. As a result, the capacity of the positive electrode active material can be improved, thereby improving the energy density of the battery.
[0014] In any embodiment of the present application, the 110 lattice spacing d of the perovskite structure 110 for Optional When the 110 lattice spacing d 110 When the given range is met, it can be proved that the ternary cathode material contains complete Lat M 1-t Therefore, the positive electrode active material of the embodiment of the present application is applied to a secondary battery, which can significantly improve the energy density and cycle performance of the battery.
[0015] In any embodiment of the present application, the volume particle size distribution span of the positive electrode active material SPAN = (Dv90-Dv10) / Dv50, then SPAN ≥ 1.1, optionally, SPAN ≥ 1.2. As a result, the positive electrode active material can have a higher powder compaction density, thereby increasing the volume energy density of the positive electrode active material. Therefore, the positive electrode active material of the embodiment of the present application is applied to a secondary battery, which can further increase the energy density of the battery.
[0016] In any embodiment of the present application, the volume particle size distribution Dv90 of the positive electrode active material is 15 μm-25 μm, and can be optionally 18 μm-22 μm.
[0017] In any embodiment of the present application, the volume particle size distribution Dv50 of the positive electrode active material is 6 μm-14 μm, and optionally 8 μm-12 μm.
[0018] In any embodiment of the present application, the volume particle size distribution Dv10 of the positive electrode active material is 1 μm-5 μm, and optionally 2 μm-4 μm.
[0019] When one or more of the volume particle size distributions Dv90, Dv50, and Dv10 of the positive electrode active material meet the given ranges, the positive electrode active material can have a wider particle size distribution. This allows the positive electrode active material to have a higher powder compaction density, thereby increasing the volume energy density of the positive electrode active material and, in turn, the energy density of the battery.
[0020] In any embodiment of the present application, the powder compaction density of the positive electrode active material under 5 tons of pressure is greater than or equal to 3.5g / cc, and can be optionally 3.5g / cc-3.7g / cc. This can make the positive electrode active material have a higher volume energy density. Therefore, the positive electrode active material of the embodiment of the present application is used in a secondary battery, which can further improve the energy density of the battery.
[0021] In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode active material, comprising the following steps.
[0022] A precursor solution is provided, wherein the precursor solution includes a mixed solution of nickel salt, cobalt salt, manganese salt and lanthanum salt.
[0023] Mix the precursor solution evenly with a precipitating agent and a complexing agent so that nickel salt, cobalt salt, manganese salt and lanthanum salt undergo a coprecipitation reaction in the presence of the precipitating agent and the complexing agent, obtaining a ternary cathode material precursor doped with La.
[0024] Disperse the ternary cathode material precursor doped with La and the M source evenly in a solvent, and obtain a mixture through drying. M includes one or more of Ca, Ti, Fe, Mg, Zn, Zr, Nb, W, Ta, Mo, Cu.
[0025] After mixing the mixture evenly with a lithium source, conduct calcination to obtain a cathode active material.
[0026] The cathode active material includes a ternary cathode material; the ternary cathode material includes a layered crystal structure and a perovskite structure. Optionally, the perovskite structure includes La t M 1-t NiO3-type perovskite structure, where 0 < t < 1, and M includes one or more of Ca, Ti, Fe, Mg, Zn, Zr, Nb, W, Ta, Mo, Cu.
[0027] The cathode active material prepared by the method of the embodiments of the present application includes a layered crystal structure and a perovskite structure. The perovskite structure has the property of zero strain. During charge and discharge cycles, this "zero strain" can inhibit the structural damage caused by the back-and-forth expansion and contraction of the electrode material. Therefore, when the ternary cathode material includes a perovskite structure, on the one hand, the perovskite structure can coexist with the layered crystal structure, thus maintaining the stability of the layered crystal structure. On the other hand, it can serve as a stress release site to release the stress accumulated by the ternary cathode material during the cycle, thereby inhibiting the cracking of the ternary cathode material particles and enhancing the structural stability of the ternary cathode material. Thereby, the structural stability of the cathode active material during high-voltage charge and discharge cycles can be enhanced, and the capacity performance of the cathode active material can be improved, enabling the battery to have both high energy density and good cycle performance.
[0028] In any implementation manner of the present application, the lanthanum salt includes one or more of sulfates, nitrates, carbonates, oxalates, chlorides containing the La element. The lanthanum salt selected from the above types can be evenly doped inside the ternary cathode material precursor particles through a coprecipitation reaction. Thereby, it is beneficial to maintain the integrity of the layered crystal structure and the perovskite structure in the ternary cathode material, thus being beneficial to improving the cycle performance of the battery.
[0029] In any implementation manner of the present application, the precipitating agent includes one or more of sodium hydroxide, sodium carbonate, potassium carbonate, potassium hydroxide.
[0030] In any embodiment of the present application, the complexing agent includes one or more of ammonia water, ammonium chloride, ammonium sulfate, urea, citric acid, and ethylenediaminetetraacetic acid.
[0031] In any embodiment of the present application, the pH of the coprecipitation reaction is 10-13, optionally 11-12, and the reaction temperature of the coprecipitation reaction is 30°C-80°C.
[0032] By regulating at least one of the precipitant, complexing agent, pH of the coprecipitation reaction, and reaction temperature to meet the above reaction conditions, the composition and structure of the ternary positive electrode material precursor can be regulated. As a result, the ternary positive electrode material precursor can be allowed to have a higher nickel content and a suitable particle size, thereby allowing the positive electrode active material to have a high energy density. Therefore, the positive electrode active material prepared in the embodiment of the present application is applied to a secondary battery to improve the energy density of the battery.
[0033] In any embodiment of the present application, the volume particle size distribution Dv50 of the La-doped ternary cathode material precursor is 5 μm-15 μm. When the volume particle size distribution Dv50 of the La-doped ternary cathode material precursor satisfies the given range, the structure of the ternary cathode material can be regulated, thereby facilitating the formation of a stable symbiotic structure between the layered crystal structure and the perovskite structure. This is beneficial for improving the structural stability of the cathode active material, thereby improving the cycle performance of the battery.
[0034] In any embodiment of the present application, the M source includes one or more of sulfates, carbonates, oxides, hydroxides, halides, nitrates, silicates, acetates, and oxalates containing the element M. The M source selected from the above types can be smoothly doped into the ternary positive electrode material and form a stable La2+ bond with the La element. t M 1-t NiO3 type perovskite structure. This is beneficial to improve the structural stability of the ternary positive electrode material, thereby improving the cycle performance of the battery.
[0035] In any embodiment of the present application, in the mixture, the molar ratio of La element to M element is 1 to 2. This is beneficial to improving the structural stability of the positive electrode active material, thereby improving the cycle performance of the battery.
[0036] In any embodiment of the present application, the drying temperature is 50° C.-90° C. This is not only beneficial for uniform mixing of the M source and the ternary cathode material precursor, but also beneficial for maintaining the stability of the ternary cathode material precursor structure.
[0037] In any embodiment of the present application, the lithium source includes one or more of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4, and CH3COOLi.
[0038] Optionally, the molar amount of Li element contained in the lithium source is n Li Can satisfy 1.0≤n Li / n Me ≤1.2, where n Me It represents the total molar amount of Ni, Co and Mn elements in the La-doped ternary cathode material precursor.
[0039] In this way, the structure of the ternary positive electrode material can be regulated to prepare a high nickel content ternary positive electrode material with excellent electrochemical performance.
[0040] In any embodiment of the present application, after the mixture is uniformly mixed with the lithium source, calcination is performed to obtain a positive electrode active material, including: after the mixture is uniformly mixed with the lithium source, calcination at 700°C-1000°C, optionally 800°C-900°C for 1h-3h, optionally 1.5h-2h, and then calcination at 600°C-800°C, optionally 650°C-750°C for 8h-20h, optionally 10h-15h to obtain the positive electrode active material, and the calcination atmosphere is an oxygen-containing atmosphere. This embodiment adopts a step-by-step calcination process, and the higher temperature calcination process is conducive to the generation of stable La t M 1-t NiO3 type perovskite structure, the lower temperature calcination process is conducive to the growth of layered crystal structure. t M 1-t The NiO3-type perovskite structure forms a stable symbiotic structure with the layered crystal structure, thereby improving the structural stability of the positive electrode active material and further improving the cycle performance of the battery.
[0041] In a third aspect, embodiments of the present application provide a positive electrode sheet comprising a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector. The positive electrode film layer comprises the positive electrode active material of the first aspect, or the positive electrode active material prepared according to the method of the second aspect.
[0042] In a fourth aspect, an embodiment of the present application provides a battery comprising the positive electrode sheet of the third aspect. Thus, the battery of the embodiment of the present application can have both high energy density and good cycle performance.
[0043] In a fifth aspect, an embodiment of the present application provides an electrical device comprising the battery according to the fourth aspect of the present application.
[0044] The electric device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.
[0046] FIG1 is a schematic diagram of an embodiment of a battery cell provided in the present application.
[0047] FIG2 is an exploded schematic diagram of an embodiment of a battery cell provided in the present application.
[0048] FIG3 is a schematic diagram of an embodiment of a battery module provided in the present application.
[0049] FIG4 is a schematic diagram of an embodiment of a battery pack provided in the present application.
[0050] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .
[0051] FIG6 is a schematic diagram of an embodiment of an electric device including the battery cell provided in the present application as a power source.
[0052] In the accompanying drawings, which are not necessarily drawn to scale, the reference numerals are as follows: 1. battery pack; 2. upper housing; 3. lower housing; 4. battery module; 5. battery cell; 51. housing; 52. electrode assembly; 53. cover plate. DETAILED DESCRIPTION
[0053] Below, with appropriate reference to the accompanying drawings, the embodiments of the positive electrode active material and its preparation method, the positive electrode sheet, the battery and the electric device containing the same are specifically disclosed. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0054] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0055] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present application.
[0056] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of this application.
[0057] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0058] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0059] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0060] Unless otherwise specified, in this application, the terms "first", "second", etc. are used to distinguish different objects rather than to describe a specific order or a primary-secondary relationship.
[0061] In this application, the terms "plurality", "multiple" and the like refer to two or more.
[0062] Unless otherwise specified, the terms used in this application have the common meanings that are commonly understood by those skilled in the art.
[0063] Unless otherwise stated, the numerical values of the various parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise stated, the test temperature of each parameter is 25°C.
[0064] Unless otherwise specified, all ratio parameters involved in this application are compared in the same unit. For example, the thickness ratio of A to B is 1.2:1, and the thickness units of A and B are the same.
[0065] As used herein, the term "source" refers to a compound that is the source of an element. Examples of the "source" include, but are not limited to, carbonates, sulfates, nitrates, elements, halides, oxides, and hydroxides.
[0066] positive electrode active material
[0067] Increasing the battery's charge cutoff voltage is considered an effective way to increase battery energy density. Currently, the positive electrode materials of commercial high-capacity lithium-ion batteries mainly include ternary positive electrode materials (such as nickel-cobalt-manganese ternary positive electrode materials or nickel-cobalt-aluminum ternary positive electrode materials). However, the cation mixing phenomenon of ternary positive electrode materials under high-voltage charge and discharge cycles is more serious, causing the ternary positive electrode materials to undergo irreversible phase changes during the charge and discharge process, thereby exacerbating the changes in the crystal structure, causing the ternary positive electrode material particles to crack, pulverize, and deactivate, thereby deteriorating the battery's cycle performance.
[0068] To this end, a first aspect of an embodiment of the present application provides a positive electrode active material, including a ternary positive electrode material. The ternary positive electrode material comprises a layered crystal structure and a perovskite structure.
[0069] Herein, the layered crystal structure has a meaning well known in the art, and may include a layered crystal structure generally possessed by a ternary positive electrode material, for example, a layered crystal structure belonging to the space group R-3m.
[0070] As used herein, the perovskite structure may refer to a structure identical or similar to the perovskite CaTiO3, and may be represented by the ABO3 type. The perovskite structure may be a cubic system, with O ions and larger-radius A ions forming a cubic closest-packed structure, while smaller-radius B ions fill the quarter of the octahedral voids. For example, the A element may include one or more of La, Ca, Ti, Fe, Mg, Zn, Zr, Nb, W, Ta, Mo, and Cu, and the B element may include a transition metal element, such as Ni.
[0071] In the positive electrode active material of the present invention, the perovskite structure can be uniformly distributed within the ternary positive electrode material. The layered crystal structure and the perovskite structure can coexist within the ternary positive electrode material, forming a coherent crystal phase, where the lattices of the two phases are connected. The perovskite structure and the layered crystal structure can be characterized by X-ray diffraction (XRD).
[0072] Without intending to be limited by any theory or explanation, the perovskite structure has the property of zero strain. The so-called "zero strain" means that the lattice constant and volume changes of its crystals when lithium ions are inserted or removed are very small, for example, less than 1%. In other words, during the charge and discharge cycle, this "zero strain" can suppress the destruction of the structure caused by the expansion and contraction of the electrode material. Therefore, when the ternary positive electrode material contains a perovskite structure, the perovskite structure can, on the one hand, coexist with the layered crystal structure, thereby maintaining the stability of the layered crystal structure, and on the other hand, it can serve as a stress release site to release the stress accumulated in the ternary positive electrode material during the cycle, thereby suppressing the cracking of the ternary positive electrode material particles and improving the structural stability of the ternary positive electrode material. As a result, the structural stability of the positive electrode active material under high voltage charge and discharge cycles can be improved, and the capacity of the positive electrode active material can be improved, so that the battery has both high energy density and good cycle performance.
[0073] In some embodiments, the perovskite structure may include La t M 1-t NiO3 type perovskite structure, wherein 0<t<1, and M includes one or more of Ca, Ti, Fe, Mg, Zn, Zr, Nb, W, Ta, Mo, and Cu.
[0074] Without intending to be bound by any theory or interpretation, La t M 1-tThe NiO3-type perovskite structure has the property of zero strain and a suitable volume, and can be doped into the layered crystal structure of the ternary cathode material to form a stable symbiotic structure with the layered crystal structure. Thereby, the structural stability of the ternary cathode material can be further improved, and thus the cycle performance of the battery can be improved.
[0075] In some embodiments, in the ternary cathode material, the molar ratio of Ni element among the transition metal elements is greater than or equal to 0.6. For example, it can be 0.6, 0.8, 0.9, 0.95, and so on.
[0076] In some embodiments, the ternary cathode material may have the general formula Li 1+a [Ni x Co y Mn z La m M n O2, where 0.6 ≤ x < 1, 0 ≤ y ≤ 0.4, 0 ≤ z ≤ 0.4, 0.05 ≤ a ≤ 0.1, 0 < m ≤ 0.1, 0 < n ≤ 0.1, and x + y + z + m + n = 1. In the ternary cathode material Li 1+a [Ni x Co y Mn z La m M n O2, the contained La t M 1-t NiO3-type perovskite structure can be represented by La m M n Ni (m+n) O 3(m+n) for expression.
[0077] Optionally, in some embodiments, 0.02 ≤ m ≤ 0.05 and 1 ≤ m / n ≤ 2.
[0078] Without being intended to be limited by any theory or explanation, the above ternary cathode material has a high nickel content and thus has a high theoretical capacity. In addition, the above ternary cathode material also contains an appropriate amount of La t M 1-t NiO3-type perovskite structure. The appropriate amount of La t M 1-t NiO3-type perovskite structure can effectively stabilize the layered crystal structure of the ternary cathode material, thereby improving the structural stability of the ternary cathode material during high-voltage charge-discharge cycling. Thereby, it is beneficial to reduce the risk of cracking of the ternary cathode material particles and improve the capacity performance and cycle stability of the ternary material. Therefore, when the positive electrode active material of the embodiment of the present application is applied to a secondary battery, the energy density and cycle performance of the battery can be significantly improved.
[0079] In some embodiments, based on the total molar amount of the ternary positive electrode material, the molar percentage of the perovskite structure can be 1%-10%, for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range consisting of any two of the above values.
[0080] Optionally, in some embodiments, based on the total molar amount of the ternary positive electrode material, the molar percentage of the perovskite structure can also be 2%-5%, for example, it can be 2%, 2.2%, 2.5%, 2.7%, 3%, 3.1%, 3.4%, 3.6%, 3.8%, 4%, 4.1%, 4.3%, 4.5%, 4.7%, 5%, or a range consisting of any two of the above values.
[0081] Without intending to be bound by any theory or explanation, when the molar percentage of the perovskite structure in the ternary cathode material is within the above-mentioned suitable range, the ternary cathode material can maintain the stability of the layered crystal structure while having good lithium ion diffusion performance. This can enhance the capacity of the cathode active material and thus improve the energy density of the battery.
[0082] The molar percentage of the perovskite structure has a meaning well known in the art. The perovskite structure and its molar percentage in the ternary cathode material can be determined by equipment and methods known in the art. For example, the perovskite structure and its molar percentage can be determined by performing phase analysis on the ternary cathode material using an X-ray diffraction (XRD) instrument.
[0083] In some embodiments, the 110 dimensional interplanar spacing d of the perovskite structure is 110 Can be For example, it can be Or a range consisting of any two of the above values.
[0084] Optionally, in some embodiments, the 110 lattice spacing d of the perovskite structure 110 You can also For example, it can be Or a range consisting of any two of the above values.
[0085] Without intending to be bound by any theory or explanation, when the 110 lattice spacing d 110 When the given range is met, it can be proved that the ternary cathode material contains complete La t M 1-t Therefore, the positive electrode active material of the embodiment of the present application is applied to a secondary battery, which can significantly improve the energy density and cycle performance of the battery.
[0086] The 110-degree interplanar spacing d of the perovskite structure 110It has a meaning well known in the art and can be measured by equipment and methods known in the art, for example, by transmission electron microscopy (TEM).
[0087] In some embodiments, the volume particle size distribution span of the positive electrode active material SPAN = (Dv90-Dv10) / Dv50, then SPAN ≥ 1.1, for example, SPAN can be 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, or a range consisting of any two of the above values.
[0088] Optionally, in some embodiments, SPAN ≥ 1.2, for example, SPAN can be 1.2-2.0, 1.3-2.0, 1.4-2.0, 1.5-2.0, 1.6-2.0, 1.7-2.0, 1.8-2.0, 1.9-2.0, 1.2-1.9, 1.3-1.8, 1.4-1.7, 1.5-1.6, and so on.
[0089] Without intending to be bound by any theory or explanation, when the positive electrode active material has the above-mentioned large volume particle size distribution span SPAN value, it means that the positive electrode active material has a wider particle size distribution. As a result, the positive electrode active material can have a higher powder compaction density, thereby increasing the volume energy density of the positive electrode active material. Therefore, the positive electrode active material of the embodiment of the present application is applied to a secondary battery, which can further increase the energy density of the battery.
[0090] In some embodiments, the volume particle size distribution Dv90 of the positive electrode active material may be 15 μm to 25 μm. For example, Dv90 may be 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, or a range consisting of any two of the foregoing values.
[0091] Alternatively, in some embodiments, the volume particle size distribution Dv90 of the positive electrode active material may be 18 μm to 22 μm. For example, Dv90 may be 18 μm, 18.5 μm, 19 μm, 19.5 μm, 20 μm, 20.5 μm, 21 μm, 21.5 μm, 22 μm, or a range consisting of any two of the above values.
[0092] In some embodiments, the volume particle size distribution Dv50 of the positive electrode active material may be 6 μm to 14 μm. For example, Dv50 may be 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or a range consisting of any two of the above values.
[0093] Alternatively, in some embodiments, the volume particle size distribution Dv50 of the positive electrode active material may also be 8 μm-12 μm. For example, Dv50 may be 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, or a range consisting of any two of the above values.
[0094] In some embodiments, the volume particle size distribution Dv10 of the positive electrode active material may be 1 μm-5 μm. For example, Dv10 may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or a range consisting of any two of the above values.
[0095] Alternatively, in some embodiments, the volume particle size distribution Dv10 of the positive electrode active material may be 2 μm to 4 μm. For example, Dv10 may be 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, or a range consisting of any two of the above values.
[0096] Without intending to be bound by any theory or explanation, when one or more of the volume particle size distributions Dv90, Dv50, and Dv10 of the positive electrode active material falls within the given ranges, the positive electrode active material can have a wider particle size distribution. This can allow the positive electrode active material to have a higher powder compaction density, thereby increasing the volume energy density of the positive electrode active material and, in turn, the energy density of the battery.
[0097] The volume particle size distribution of the positive electrode active material has a meaning well known in the art and can be measured by equipment and methods known in the art. Among them, the volume particle size distribution Dv50 refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%; the volume particle size distribution Dv10 refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 10%; and the volume particle size distribution Dv90 refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 90%. The volume particle size distribution Dv50, Dv10, and Dv90 of the positive electrode active material can all be measured using laser diffraction particle size analysis. For example, with reference to standard GB / T 19077-2016, a laser particle size analyzer (such as Malvern Master Size 3000) is used for measurement.
[0098] In some embodiments, the powder compaction density of the positive electrode active material under 5 tons of pressure is greater than or equal to 3.5g / cc, and can be optionally 3.5g / cc-3.7g / cc. When the powder compaction density of the positive electrode active material under 5 tons of pressure meets the given range, the positive electrode active material can have a higher volume energy density. Therefore, the positive electrode active material of the embodiment of the present application can be used in a secondary battery to further improve the energy density of the battery.
[0099] The powder compaction density of the positive electrode active material under a pressure of 5 tons has a meaning well known in the art and can be measured by equipment and methods known in the art. As an example, the compaction density of the positive electrode active material under a pressure of 5 tons (i.e., under a pressure of 5T) can be determined with reference to GB / T 24533-2009. Specifically, a certain amount of positive electrode active material powder can be placed in a special compaction mold, and then the mold can be placed on a compaction density instrument. A pressure of 5T is applied, and the thickness of the powder under a pressure of 5T (the thickness after pressure relief) is read on the equipment, and the powder compaction density ρ of the positive electrode active material is calculated by ρ=m / v.
[0100] Preparation method
[0101] A second aspect of an embodiment of the present application provides a method for preparing a positive electrode active material, comprising the following steps S10 to S40.
[0102] S10, providing a precursor solution, wherein the precursor solution includes a mixed solution of nickel salt, cobalt salt, manganese salt and lanthanum salt.
[0103] In step S10, providing the precursor solution may include mixing a nickel salt solution, a cobalt salt solution, a manganese salt solution, and a lanthanum salt solution to obtain a mixed solution; or may include mixing and dissolving a nickel salt, a cobalt salt, a manganese salt, and a lanthanum salt in deionized water to obtain a mixed solution. This is not limited herein. The nickel salt, cobalt salt, manganese salt, and lanthanum salt may be selected from soluble nickel salts, cobalt salts, manganese salts, and lanthanum salts known in the art. Examples of soluble nickel salts may include one or more nickel-containing sulfates, nitrates, acetates, carbonates, oxalates, citrates, and chlorides. Examples of soluble cobalt salts may include one or more cobalt-containing sulfates, nitrates, acetates, carbonates, oxalates, citrates, and chlorides. Examples of soluble manganese salts may include one or more manganese-containing sulfates, nitrates, acetates, carbonates, oxalates, citrates, and chlorides. Those skilled in the art may select the appropriate salt based on actual needs, and this is not limited herein. The ratio of nickel salt, cobalt salt, manganese salt and lanthanum salt can be adjusted according to actual needs. For example, the ratio of nickel salt, cobalt salt, manganese salt and lanthanum salt used to prepare the precursor solution can be adjusted according to the molar ratio of Ni element, Co element, Mn element and La element in the ternary positive electrode material to be prepared. The concentration of the precursor solution is not specifically limited and can be adjusted by those skilled in the art as needed. As an example, the total molar concentration of Ni element, Co element, Mn element and La element in the precursor solution can be 0.1 mol / L to 10 mol / L.
[0104] S20. Mix the precursor solution, precipitating agent, and complexing agent uniformly so that nickel salt, cobalt salt, manganese salt, and lanthanum salt undergo a coprecipitation reaction in the presence of the precipitating agent and complexing agent to obtain a ternary cathode material precursor doped with La.
[0105] In step S20, examples of the precipitating agent and complexing agent may include one or more precipitating agents and complexing agents known in the art, which can be selected by those skilled in the art according to actual needs and are not limited herein. In one embodiment, 10%-50% pure water can be added to a 100 L reaction kettle, and a certain amount of precipitating agent solution is added under stirring to a concentration of 0.2 mol / L to 0.6 mol / L, optionally 0.3 mol / L to 0.5 mol / L; the precursor solution, precipitating agent solution, and complexing agent solution are added to the reaction kettle at a certain rate, keeping the pH of the solution in the reaction kettle and the concentration of the complexing agent basically unchanged, so that nickel salt, cobalt salt, manganese salt, and lanthanum salt undergo a coprecipitation reaction in the presence of the precipitating agent and complexing agent, and then through centrifugation, washing, filtration, and drying, a ternary cathode material precursor doped with La is obtained. The concentration of the above precipitating agent solution can be 0.1 mol / L to 20 mol / L; the concentration of the complexing agent solution can be 0.1 mol / L to 10 mol / L.
[0106] S30. Disperse the ternary cathode material precursor doped with La and the M source uniformly in a solvent, and dry to obtain a mixture. M includes one or more of Ca, Ti, Fe, Mg, Zn, Zr, Nb, W, Ta, Mo, and Cu.
[0107] In step S30, the solvent may include solvents known in the art that can dissolve the M source. For example, the solvent may include one or more of deionized water, ethanol, propanol, isopropanol, ethylene glycol, etc. Those skilled in the art can select according to the type of the M source and are not limited herein.
[0108] S40. After mixing the mixture and the lithium source uniformly, calcine to obtain a cathode active material. The cathode active material includes a ternary cathode material; the ternary cathode material includes a layered crystal structure and a perovskite structure. Optionally, the perovskite structure includes La t M 1-t NiO3-type perovskite structure, where 0 < t < 1, and M includes one or more of Ca, Ti, Fe, Mg, Zn, Zr, Nb, W, Ta, Mo, and Cu.
[0109] In step S40, in the ternary cathode material, the molar doping amount of the La element can be greater than 0 and less than or equal to 0.1, optionally 0.02 - 0.05.
[0110] The positive electrode active material prepared by the method of the embodiment of the present application comprises a layered crystal structure and a perovskite structure. The perovskite structure has the property of zero strain. During the charge and discharge cycle, this “zero strain” can suppress the destruction of the structure caused by the expansion and contraction of the electrode material. Therefore, when the ternary positive electrode material comprises a perovskite structure, the perovskite structure can, on the one hand, coexist with the layered crystal structure, thereby maintaining the stability of the layered crystal structure, and on the other hand, it can serve as a stress release site to release the stress accumulated in the ternary positive electrode material during the cycle, thereby suppressing the cracking of the ternary positive electrode material particles and improving the structural stability of the ternary positive electrode material. Thus, the structural stability of the positive electrode active material under high voltage charge and discharge cycles can be improved, and the capacity of the positive electrode active material can be improved, so that the battery has both high energy density and cycle performance.
[0111] In some embodiments, the lanthanum salt may include one or more of sulfates, nitrates, carbonates, oxalates, and chlorides containing the La element.
[0112] The lanthanum salts selected from the above types can be uniformly doped within the ternary cathode material precursor particles through a co-precipitation reaction. This helps maintain the integrity of the layered crystal structure and perovskite structure in the ternary cathode material, thereby improving the battery's cycling performance.
[0113] In some embodiments, the precipitant may include one or more of sodium hydroxide, sodium carbonate, potassium carbonate, and potassium hydroxide.
[0114] In some embodiments, the complexing agent may include one or more of ammonia, ammonium chloride, ammonium sulfate, urea, citric acid, and ethylenediaminetetraacetic acid (EDTA).
[0115] In some embodiments, the pH of the co-precipitation reaction may be 10-13, optionally 11-12, and the reaction temperature of the co-precipitation reaction may be 30°C-80°C.
[0116] Without intending to be bound by any theory or explanation, by regulating at least one of the precipitant, complexing agent, pH of the coprecipitation reaction, and reaction temperature to meet the above reaction conditions, the composition and structure of the ternary positive electrode material precursor can be regulated. As a result, the ternary positive electrode material precursor can be allowed to have a higher nickel content and a suitable particle size, thereby allowing the positive electrode active material to have a high energy density. Therefore, the positive electrode active material prepared in the embodiment of the present application is applied to a secondary battery to improve the energy density of the battery.
[0117] In some embodiments, the volume particle size distribution Dv50 of the La-doped ternary cathode material precursor may be 5 μm-15 μm. For example, Dv50 may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or a range consisting of any two of the above values.
[0118] Without intending to be bound by any theory or explanation, when the volume particle size distribution Dv50 of the La-doped ternary cathode material precursor falls within the given range, the structure of the ternary cathode material can be regulated, thereby facilitating the formation of a stable symbiotic structure between the layered crystal structure and the perovskite structure. This, in turn, helps improve the structural stability of the cathode active material, thereby enhancing the cycling performance of the battery.
[0119] In some embodiments, the M source may include one or more of sulfates, carbonates, oxides, hydroxides, halides, nitrates, silicates, acetates, and oxalates containing the M element.
[0120] Without intending to be bound by any theory or explanation, the M source selected from the above types can be smoothly doped into the ternary cathode material and form a stable La t M 1-t NiO3 type perovskite structure. This is beneficial to improve the structural stability of the ternary positive electrode material, thereby improving the cycle performance of the battery.
[0121] In some embodiments, in the mixture, the molar ratio of La element to M element may be 1-2, for example, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, or a range consisting of any two of the above values.
[0122] Without intending to be bound by any theory or explanation, when the molar ratio of La element to M element satisfies the given range, La t M 1-t The NiO3 perovskite structure has a suitable volume, which is conducive to the La t M 1-t The NiO3-type perovskite structure is doped into the layered crystal structure of the ternary cathode material, forming a stable symbiotic structure with the layered crystal structure. This helps to improve the structural stability of the cathode active material, thereby improving the cycle performance of the battery.
[0123] In some embodiments, the drying temperature may be 50° C.-90° C. This is not only beneficial for uniform mixing of the M source and the ternary cathode material precursor, but also beneficial for maintaining the stability of the structure of the ternary cathode material precursor.
[0124] In some embodiments, the lithium source may include one or more of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4, and CH3COOLi. The molar amount of Li element contained in the lithium source is n Li Can satisfy 1.0≤n Li / n Me ≤1.2, where n Me represents the total molar amount of Ni, Co, and Mn in the La-doped ternary cathode material precursor. This allows for the structure of the ternary cathode material to be regulated, resulting in a high-nickel content ternary cathode material with excellent electrochemical performance.
[0125] In some embodiments, step S40, after uniformly mixing the mixture with the lithium source, calcining to obtain a positive electrode active material, can specifically include: after uniformly mixing the mixture with the lithium source, calcining at 700°C-1000°C, optionally 800°C-900°C for 1h-3h, optionally 1.5h-2h, and then calcining at 600°C-800°C, optionally 650°C-750°C for 8h-20h, optionally 10h-15h to obtain the positive electrode active material, and the calcination atmosphere is an oxygen-containing atmosphere, for example, may include but is not limited to air or oxygen atmosphere.
[0126] Without intending to be bound by any theory or explanation, this embodiment adopts a step-by-step calcination process, and a higher temperature calcination process is conducive to the formation of stable La t M 1-t NiO3 type perovskite structure, the lower temperature calcination process is conducive to the growth of layered crystal structure. t M 1-t The NiO3-type perovskite structure forms a stable symbiotic structure with the layered crystal structure, thereby improving the structural stability of the positive electrode active material and further improving the cycle performance of the battery.
[0127] Positive electrode
[0128] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector. The positive electrode film layer comprises the positive electrode active material of the first aspect, or the positive electrode active material prepared according to the method of the second aspect. The positive electrode plate of an embodiment of the present application comprises the positive electrode active material of the first aspect, or the positive electrode active material prepared according to the method of the second aspect, and is applied to a secondary battery, so that the secondary battery can have both high energy density and good cycle performance.
[0129] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application does not particularly limit the type of the positive electrode conductive agent. For example, the positive electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0130] In some embodiments, the positive electrode film layer may further optionally include a positive electrode binder. This application does not particularly limit the type of positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin.
[0131] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, an aluminum alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0132] The positive electrode film is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying it, and cold pressing it. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).
[0133] Battery
[0134] The battery mentioned in the embodiments of the present application may include one or more battery cells to provide a single physical module with higher voltage and capacity. When there are multiple battery cells, the multiple battery cells are connected in series, in parallel or in hybrid through a busbar.
[0135] Typically, a battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode, a negative electrode, and a separator. During the charge and discharge process of the battery cell, active ions (such as lithium ions) are embedded and extracted back and forth between the positive electrode and the negative electrode. The separator is set between the positive electrode and the negative electrode to prevent the positive and negative electrodes from short-circuiting while allowing active ions to pass through. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.
[0136] In the battery cells of the embodiments of the present application, the positive electrode sheet of the electrode assembly may include the positive electrode sheet of the third aspect. The embodiments of the positive electrode sheet have been described and illustrated in detail above and will not be repeated here. It is understood that the battery cells of the embodiments of the present application can achieve the beneficial effects of any of the aforementioned embodiments of the positive electrode sheet of the embodiments of the present application.
[0137] In some embodiments, in the battery cells of the embodiments of the present application, the negative electrode sheet of the electrode assembly may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and comprising a negative electrode active material. For example, the negative electrode current collector may have two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer may be disposed on either or both of the two opposing surfaces of the negative electrode current collector.
[0138] The negative electrode active material may be any negative electrode active material known in the art for use in secondary batteries. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. Silicon-based materials may include at least one of elemental silicon, silicon oxide, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include at least one of elemental tin, tin oxide, and tin alloys.
[0139] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0140] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder. As examples, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0141] In some embodiments, the negative electrode film layer may further include other additives, such as thickeners, sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like.
[0142] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0143] The negative electrode film layer is typically formed by coating the negative electrode slurry onto the negative electrode current collector, drying it, and cold pressing it. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.
[0144] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some embodiments, the negative electrode plate of the present application also includes a protective layer covering the surface of the negative electrode film layer.
[0145] The embodiments of the present application have no particular restrictions on the type of separator used in the electrode assembly of the battery cell. Any known porous structure separator with good chemical stability and mechanical stability can be selected.
[0146] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different.
[0147] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly through a winding process or a lamination process.
[0148] In the battery cells of the embodiments of the present application, the type of electrolyte is not specifically limited and can be selected according to needs. For example, the electrolyte can be liquid, gel, or solid.
[0149] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and solvent are not specifically limited and can be selected according to actual needs.
[0150] As an example, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium bisoxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0151] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).
[0152] In some embodiments, the electrolyte may optionally include other additives. For example, the additives may include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, additives that improve battery low temperature power performance, etc.
[0153] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly through a winding process and / or a lamination process.
[0154] In some embodiments, the battery cell may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0155] In some embodiments, the outer packaging of the battery cell can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell can also be a soft shell, such as a bag-type soft shell. The soft shell can be made of plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0156] The present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square or any other shape. FIG1 shows a battery cell 5 of a square structure as an example.
[0157] In some embodiments, as shown in FIG2 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the separator may be formed into an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 may be one or more, which can be adjusted according to demand.
[0158] The preparation method of battery cells is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, separator, and negative electrode sheet can be wound and / or laminated to form an electrode assembly. The electrode assembly is then placed in an outer packaging, dried, and then injected with electrolyte. The battery cell is then vacuum packaged, allowed to stand, formed, and shaped.
[0159] In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. FIG3 is a schematic diagram of a battery module 4 as an example. As shown in FIG3 , in the battery module 4, the multiple battery cells 5 may be arranged sequentially along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. The multiple battery cells 5 may further be fixed by fasteners. Optionally, the battery module 4 may also include a housing having a storage space, and the multiple battery cells 5 are accommodated in the storage space.
[0160] In some embodiments, the battery may be a battery pack, which includes a case and battery cells. The battery cells or battery modules are housed in the case. The number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0161] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0162] Electrical devices
[0163] The embodiments of the present application also provide an electrical device, which includes a battery cell or battery provided in the embodiments of the present application. The battery cell or battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.
[0164] The electrical device can select a battery cell or a battery according to its usage requirements.
[0165] Figure 6 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.
[0166] As another example, an electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a battery cell as a power source.
[0167] Example
[0168] The following examples describe the present disclosure in more detail. These examples are intended to be illustrative only, as various modifications and variations within the scope of the present disclosure will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing. The instruments used in the examples are commercially available.
[0169] Example 1
[0170] Preparation of positive electrode active materials
[0171] (1) Nickel sulfate hexahydrate, cobalt sulfate heptahydrate, manganese sulfate monohydrate, and lanthanum nitrate were mixed and dissolved in pure water at a molar ratio w1 of 90:4:2:2 of Ni, Co, Mn, and La to obtain a precursor solution with a total concentration of 2 mol / L of Ni, Co, Mn, and La.
[0172] (2) Add 20 L of pure water to a 100 L reactor, start stirring, maintain the temperature at 50 ° C, add an appropriate amount of precipitant solution (4 mol / L NaOH solution), and adjust the pH of the solution in the reactor to 10-13.
[0173] (3) Under stirring conditions, a precursor solution, a precipitant solution (1 mol / L NaOH solution), and a complexing agent solution (2 mol / L ammonia solution) are added to the reactor at a certain rate to allow the nickel salt, cobalt salt, manganese salt, and lanthanum salt to undergo a coprecipitation reaction in the presence of the precipitant and complexing agent. During the reaction, the ammonia concentration and pH in the reactor are maintained constant. After centrifugation, washing, filtering, and drying, a ternary cathode material precursor is prepared.
[0174] (4) Adding the M source CaCl2 to the solvent deionized water and stirring uniformly, then adding the ternary cathode material precursor, heating and stirring at 50°C-90°C until the solvent is completely evaporated to obtain a mixture. The ratio w2 of the molar amount of the La element in the ternary cathode material precursor to the molar amount of the M element (Ca element) in the M source (CaCl2) is 1:1.
[0175] (5) After the mixture is fully mixed with the lithium source Li2CO3, it is calcined at 800°C for 3 hours and then at 600°C for 10 hours in an air atmosphere to obtain a positive electrode active material. The ratio w3 of the molar amount of the lithium element in the lithium source to the total molar amount of the Ni element, Co element, and Mn element in the ternary positive electrode material precursor is 1.03:0.96.
[0176] Preparation of positive electrode
[0177] The positive electrode active material Li 1.03 [Ni 0.9 Co 0.04 Mn 0.02 La 0.02 Ca 0.02 ]O2, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed uniformly in an appropriate amount of solvent N-methylpyrrolidone (NMP) in a mass ratio of 98:1:1 to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through processes such as drying, cold pressing, slitting, and cutting.
[0178] Preparation of negative electrode sheet
[0179] The negative electrode active material artificial graphite, the conductive agent carbon black (Super P), the binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 97:1:1:1 to obtain a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.
[0180] Preparation of isolation membrane
[0181] Polypropylene film is used as the isolation film.
[0182] Preparation of electrolyte
[0183] LiPF6 was dissolved in a solvent prepared by mixing ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in a ratio of 1:1:1 by volume to obtain an electrolyte with a LiPF6 concentration of 1 mol / L.
[0184] Preparation of secondary batteries
[0185] The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in sequence to obtain an electrode assembly; the electrode assembly is placed in an outer package, dried, and then injected with electrolyte. After vacuum packaging, standing, formation, shaping and other processes, a secondary battery is obtained.
[0186] Examples 2-5
[0187] Based on the preparation process of the positive electrode active material in Example 1, the type of M source was adjusted to prepare the positive electrode active materials of Examples 2-5. The preparation of the positive electrode plates, negative electrode plates, separators, electrolytes, and secondary batteries of Examples 2-5 was the same as that of Example 1. Specifically, Example 2 was based on Example 1, except that the M source was replaced with an equimolar amount of Ti(SO4)2; Example 3 was based on Example 1, except that the M source was replaced with an equimolar amount of ZnSO4; Example 4 was based on Example 1, except that the M source was replaced with an equimolar amount of WO3; and Example 5 was based on Example 1, except that the M source was replaced with an equimolar amount of Zr(SO4)2.
[0188] Examples 6-18
[0189] Based on the preparation process of the positive electrode active material in Example 1, w1 to w3 were adjusted to prepare the positive electrode active materials of Examples 6 to 18. The preparation of the positive electrode sheets, negative electrode sheets, separators, electrolytes, and secondary batteries of Examples 6 to 18 was the same as that of Example 1.
[0190] In Example 6, w1 is 90:2:2:3; w2 is 1:1; and w3 is 1.03:0.94.
[0191] In Example 7, w1 is 90:2:2:3.3; w2 is 33:27; and w3 is 1.03:0.94.
[0192] In Example 8, w1 is 90:2:2:3.5; w2 is 35:25; and w3 is 1.03:0.94.
[0193] In Example 9, w1 is 90:2:2:3.8; w2 is 38:22; and w3 is 1.03:0.94.
[0194] In Example 10, w1 is 90:2:2:4; w2 is 2:1; and w3 is 1.03:0.94.
[0195] In Example 11, w1 is 60:25:11:2; w2 is 1:1; and w3 is 1.02:0.96.
[0196] In Example 12, w1 is 75:15:6:2; w2 is 1:1; and w3 is 1.03:0.96.
[0197] In Example 13, w1 is 80:10:6:2; w2 is 1:1; and w3 is 1.04:0.96.
[0198] In Example 14, w1 is 92:3:1:2; w2 is 1:1; and w3 is 1.05:0.96.
[0199] In Example 15, w1 is 90:7:2:0.5; w2 is 1:1; and w3 is 1.03:0.99.
[0200] In Example 16, w1 is 90:5:1:2; w2 is 1:1; and w3 is 1.03:0.96.
[0201] In Example 17, w1 is 90:2:1:4; w2 is 4:3; and w3 is 1.03:0.93.
[0202] In Example 18, w1 is 88:1:1:6; w2 is 3:2; and w3 is 1.03:0.9.
[0203] The secondary batteries of Comparative Examples 1-5 are similar to those of Example 1, except that the conventional nickel-cobalt-manganese ternary positive electrode material is used as the positive electrode active material in Comparative Examples 1-5.
[0204] The chemical formula, perovskite structure and molar percentage Q, 110 lattice spacing d of the positive electrode active materials of Examples 1-18 and Comparative Examples 1-5 are shown in FIG. 110 The chemical formula of the positive electrode active material was characterized by dissolving the positive electrode active material in aqua regia and performing elemental analysis by inductively coupled plasma optical emission spectrometry (ICP, Ametek, model: SPECTROARCOSICP-OES) to obtain the ratio of each element. The chemical formula of the positive electrode active material was determined by the ratio of each element. The perovskite structure and its molar percentage Q, the 110 lattice spacing d of the perovskite structure 110 It can be characterized by the method described in the specification of this application.
[0205] Test section
[0206] Normal temperature cycle performance test
[0207] At 25°C, charge the secondary battery at a constant current of 0.5C to 4.25V, then charge it at a constant voltage of 4.25V to a cutoff current of 0.05C, let it rest for 10 minutes, then discharge it at a constant current of 0.5C to 2.8V, let it rest for 5 minutes. This is one charge and discharge cycle. Record the discharge capacity at this time as C0. Repeat this charge and discharge cycle process for the same secondary battery and record the discharge capacity C1 at the 300th cycle. The battery's cycle capacity retention rate P 300 =C1 / C0×100%. The test results are shown in Table 1.
[0208] From the test results in Table 1, it can be seen that the positive electrode active material of the embodiment of the present application has a specific structure, that is, the ternary positive electrode material contains a layered crystal structure and a perovskite structure, which can be applied to secondary batteries to effectively improve the cycle performance of the battery.
[0209] In contrast, the positive electrode active materials of Comparative Examples 1-5 do not contain a perovskite structure, and as the nickel content in the positive electrode active materials increases, the cycle performance of the batteries thereof deteriorates significantly. Therefore, the cycle performance of the secondary batteries of Comparative Examples 1-5 is far inferior to that of Examples 1-18.
[0210] For several compounds given but not listed in the examples, since their chemical properties and reaction properties when participating in electrochemical reactions are similar to those of the compounds listed in the examples, they are all suitable for the technical solution of the present invention and are therefore not listed here one by one.
[0211] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and within the scope of the technical solution of the present application, embodiments having substantially the same structure as the technical idea and exerting the same effects are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be conceived by those skilled in the art to the embodiments, and other methods constructed by combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, comprising a ternary positive electrode material, The ternary positive electrode material comprises a layered crystal structure and a perovskite structure.
2. The positive electrode active material according to claim 1, wherein The perovskite structure includes La t M 1-t a perovskite structure of the NiO3 type, where 0 < t < 1, and M includes one or more of Ca, Ti, Fe, Mg, Zn, Zr, Nb, W, Ta, Mo, and Cu.
3. The positive electrode active material according to claim 2, wherein In the ternary positive electrode material, the molar ratio of Ni element in the transition metal element is greater than or equal to 0.6; Optionally, the ternary cathode material has the general formula Li 1+a [Ni x Co y Mn z La m M n ]O2, where 0.6≤x<1, 0≤y≤0.4, 0≤z≤0.4, 0.05≤a≤0.1, 0 <m≤0.1,0<n≤0.1,x+y+z+m+n=1; More optionally, 0.02≤m≤0.05, 1≤m / n≤2.
4. The positive electrode active material according to any one of claims 1 to 3, wherein Based on the total molar amount of the ternary positive electrode material, the molar percentage of the perovskite structure is 1%-10%, and can be optionally 2%-5%.
5. The positive electrode active material according to any one of claims 1 to 4, wherein The 110° interplanar spacing d of the perovskite structure 110 for Optional 6. The positive electrode active material according to any one of claims 1 to 5, wherein The volume particle size distribution span SPAN of the positive electrode active material is SPAN=(Dv90-Dv10) / Dv50, then SPAN≥1.1, optionally, SPAN≥1.
2.
7. The positive electrode active material according to any one of claims 1 to 6, wherein The volume particle size distribution Dv90 of the positive electrode active material is 15 μm-25 μm, and can be 18 μm-22 μm; and / or The volume particle size distribution Dv50 of the positive electrode active material is 6 μm-14 μm, and can be 8 μm-12 μm; and / or The volume particle size distribution Dv10 of the positive electrode active material is 1 μm-5 μm, and can be 2 μm-4 μm.
8. The positive electrode active material according to any one of claims 1 to 7, wherein The powder compaction density of the positive electrode active material under a pressure of 5 tons is greater than or equal to 3.5 g / cc, and can be optionally 3.5 g / cc-3.7 g / cc.
9. A method for preparing a positive electrode active material, comprising: Providing a precursor solution, wherein the precursor solution includes a mixed solution of nickel salt, cobalt salt, manganese salt and lanthanum salt; The precursor solution is mixed with a precipitant and a complexing agent to make the nickel salt, cobalt salt, manganese salt and lanthanum salt undergo a coprecipitation reaction in the presence of the precipitant and the complexing agent to obtain a ternary positive electrode material precursor doped with La; The La-doped ternary cathode material precursor and the M source are uniformly dispersed in a solvent, and dried to obtain a mixture, wherein M includes one or more of Ca, Ti, Fe, Mg, Zn, Zr, Nb, W, Ta, Mo, and Cu; After the mixture is uniformly mixed with a lithium source, calcination is performed to obtain a positive electrode active material. The positive electrode active material includes a ternary positive electrode material; the ternary positive electrode material includes a layered crystal structure and a perovskite structure; optionally, the perovskite structure includes La t M 1-t NiO3-type perovskite structure, where 0 < t < 1, and M includes one or more of Ca, Ti, Fe, Mg, Zn, Zr, Nb, W, Ta, Mo, and Cu.
10. The method according to claim 9, wherein: The lanthanum salt includes one or more of sulfate, nitrate, carbonate, oxalate and chloride containing La element.
11. The method according to claim 9 or 10, wherein: The precipitating agent comprises one or more of sodium hydroxide, sodium carbonate, potassium carbonate and potassium hydroxide; and / or The complexing agent includes one or more of ammonia water, ammonium chloride, ammonium sulfate, urea, citric acid, and ethylenediaminetetraacetic acid; and / or The pH of the coprecipitation reaction is 10-13, and can be 11-12, and the reaction temperature of the coprecipitation reaction is 30° C.-80° C.; and / or The volume particle size distribution Dv50 of the La-doped ternary cathode material precursor is 5 μm-15 μm.
12. The method according to any one of claims 9 to 11, wherein: The M source includes one or more of sulfate, carbonate, oxide, hydroxide, halide, nitrate, silicate, acetate and oxalate containing the M element; and / or In the mixture, the molar ratio of La element to M element is 1-2; and / or The drying temperature is 50°C-90°C.
13. The method according to any one of claims 9 to 12, wherein: The lithium source includes one or more of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4, and CH3COOLi; Optionally, the molar amount of Li element contained in the lithium source is n Li Can satisfy 1.0≤n Li / n Me ≤1.2, where n Me It represents the total molar amount of Ni, Co and Mn in the La-doped ternary positive electrode material precursor.
14. The method according to any one of claims 9 to 13, wherein: The method comprises mixing the mixture and the lithium source uniformly and calcining to obtain a positive electrode active material, comprising: After the mixture is uniformly mixed with the lithium source, it is calcined at 700°C-1000°C, optionally 800°C-900°C for 1h-3h, optionally 1.5h-2h, and then calcined at 600°C-800°C, optionally 650°C-750°C for 8h-20h, optionally 10h-15h to obtain the positive electrode active material, and the calcination atmosphere is an oxygen-containing atmosphere.
15. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises the positive electrode active material according to any one of claims 1 to 8, or the positive electrode active material prepared by the method according to any one of claims 9 to 14.
16. A battery comprising the positive electrode sheet according to claim 15.
17. An electrical device comprising the battery according to claim 16.